A paradigm shift in the detection of bloodborne pathogens - Sonali Khanal; Manjusha Pillai; Deblina Biswas; Muhammad Torequl Islam; Rachna Verma; Kamil Kuca; Dinesh Kumar; Asim Najmi; Khalid Zoghebi; Asaad Khalid; Syam Mohan (EXCLI Journal : Experimental and Clinical Sciences)
Bloodborne pathogens (BBPs) pose formidable challenges in the realm of infectious diseases, representing significant risks to both human and animal health worldwide. The review paper provides a thorough examination of bloodborne pathogens, highlighting the serious worldwide threat they pose and the effects they have on animal and human health. It addresses the potential dangers of exposure that healthcare workers confront, which have affected 3 million people annually, and investigates the many pathways by which these viruses can spread. The limitations of traditional detection techniques like PCR and ELISA have been criticized, which has led to the investigation of new detection methods driven by advances in sensor technology. The objective is to increase the amount of knowledge that is available regarding bloodborne infections as well as effective strategies for their management and detection. This review provides a thorough overview of common bloodborne infections, including their patterns of transmission, and detection techniques.